Runaway electron mitigation by applied magnetic perturbations in RFX-mod tokamak plasmas. (13th October 2016) - Gobbin, M.; Valisa, M.; White, R.B.; Cester, D.; Marrelli, L.; Nocente, M.; Piovesan, P.; Stevanato, L.; Puiatti, M.E.; Zuin, M.
Abstract: Thanks to its advanced system for the control of magnetohydrodynamic modes, the RFX-mod device run as a tokamak is particularly suited to the study of the possible impact on runaway electron (RE) de-confinement in response to applied magnetic perturbations. This paper shows that during the flat-top phase in RFX-mod discharges, with a plasma current of I p ∼ 150 kA and a low density ( n e < 10 19 m −3 ), the amount of REs scales with the m   =  2, n   =  1 perturbation both in q ( a )  <  2 and q ( a )  >  2 plasmas. Similar results have also been obtained in post-disruption phases, but still with limited statistics. The mechanisms generating REs and the effect of magnetic perturbation (MP) on their confinement are interpreted by numerical simulations with the relativistic guiding center code ORBIT. The role played by different magnetic equilibria on the energy of REs and on their loss rates is investigated. ORBIT simulations indicate that RE-enhanced losses are associated with a raised level of stochasticity, the effect being more pronounced when the MP amplitude is higher and internally resonant.